2007
DOI: 10.1354/vp.44-2-185
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and Virus Tissue Distribution of Turkey Origin Reoviruses in Experimentally Infected Turkey Poults

Abstract: Abstract. The pathogenesis of 4 isolates of turkey-origin reovirus (NC/SEP-R44/03, NC/98, TX/98, and NC/85) and 1 chicken-origin reovirus (1733) was examined by infecting specific pathogen free (SPF) poults. These turkey-origin reovirus (TRV) isolates were collected from turkey flocks experiencing poult enteritis and are genetically distinct from previously reported avian reoviruses. Microscopic examination of the tissues collected from the TRV-infected poults revealed different degrees of bursal atrophy chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 52 publications
(112 reference statements)
3
21
0
Order By: Relevance
“…Three routes of inoculation (oral, intratracheal and footpad) were used. These routes of inoculation have been used in previous studies on reovirus infection in chickens (Islam et al, 1988;Jones et al, 1994) and turkeys (Al- Afaleq & Jones, 1989;Pantin-Jackwood et al, 2007). Although 1-day-old poults in Experiment 1 were positive for reovirus before inoculation, we continued with the experiment because several years of diagnostic PCR testing of faeces have indicated that Minnesota poults are usually positive for reovirus and our intent was to evaluate the effect of TARVs on turkeys raised in Minnesota.…”
Section: Discussionmentioning
confidence: 99%
“…Three routes of inoculation (oral, intratracheal and footpad) were used. These routes of inoculation have been used in previous studies on reovirus infection in chickens (Islam et al, 1988;Jones et al, 1994) and turkeys (Al- Afaleq & Jones, 1989;Pantin-Jackwood et al, 2007). Although 1-day-old poults in Experiment 1 were positive for reovirus before inoculation, we continued with the experiment because several years of diagnostic PCR testing of faeces have indicated that Minnesota poults are usually positive for reovirus and our intent was to evaluate the effect of TARVs on turkeys raised in Minnesota.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue sections were cut (4 μm thick) from paraffin-embedded tissue samples and mounted on charged glass slides (Superfrost/Plus; Fisher Scientific). Deparaffinization, antigen retrieval and blocking procedures have been previously described [24]. A 1:2,000 dilution of a mouse-derived monoclonal antibody (P13C11) specific for a type A influenza virus nucleoprotein (developed at Southeast Poultry Research Laboratory, USDA) was applied and allowed to incubate for 2 hours at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous viruses have been detected in or isolated from the intestinal tract of poultry (both diseased and healthy), and have subsequently been implicated in poultry enteric disease. These viruses include the avian reoviruses, rotaviruses, astroviruses and coronaviruses; despite these diagnostic efforts and viral descriptions, the role these viruses play in the enteric syndromes are still poorly understood (Guy, 1998;Pantin-Jackwood et al, 2008a;Pantin-Jackwood et al, 2007a;Pantin-Jackwood et al, 2008b;Pantin-Jackwood et al, 2007b;Reynolds et al, 1987;Spackman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%